Analisis Dampak Pengeluaran Pemerintah Sektor Publik Terhadap Pertumbuhan Ekonomi Inklusif Di Sumatera Barat - Muhammad Irwanda; Urmatul Uska Akbar (Media Riset Ekonomi Pembangunan (MedREP), 2025)
This study aims to analyze the effect of public sector government expenditure on inclusive economic growth in West Sumatra Province. The main focus of this research is on four independent variables—government spending in the education, health, and infrastructure sectors, as well as the open unemployment rate—and their relationship with the dependent variable, the Inclusive Economic Growth Index (IEGI). The study utilizes panel data from 19 districts/cities in West Sumatra covering the period from 2017 to 2023. The analysis method applied is panel data regression, with model selection based on the Chow test, Hausman test, and classical assumption tests. The results show that government spending in the education sector has a positive but insignificant effect, spending in the health sector has a negative and insignificant effect, infrastructure spending has a positive and significant effect, and the open unemployment rate has a negative and significant effect on inclusive economic growth. Simultaneously, the four variables have a significant impact on the IEGI in West Sumatra. These findings highlight the importance of well-targeted regional government budget allocations in promoting equitable and inclusive economic development.